Building an intelligence-led security program - Liska, Allan (Syngress is an imprint of Elsevier, 2015)
Adding cyber threat intelligence can help security teams uncover events not detected by traditional security platforms and correlate seemingly disparate events across the network. This book will show you how to implement an intelligence-led program in your enterprise on any budget. Topics include: a roadmap and direction on how to build an intelligence-led information security program to protect your company, understanding your network through logs and client monitoring so you can effectively evaluate threat intelligence; using popular tools such as BIND, SNORT, squid, STIX, TAXII, CyBox, and splunk to conduct network intelligence. --